Learning about 'inclusive' pedagogies through a special school placement. (4th May 2022) - Maher, Anthony J.; Thomson, Alan; Parkinson, Samantha; Hunt, Sarah; Burrows, Adam
ABSTRACT: Background: It is well-established that traditional approaches to initial teacher education do not adequately prepare physical education (PE) teachers for teaching pupils with disabilities. Consequently, pupils with disabilities participate less frequently and in fewer PE activities than their age peers. School-based placements, which form a cornerstone of the professional socialisation phase of teacher education, can help to prepare prospective and pre-service teachers for the demands of working in educational settings. We should not assume, though, that placing prospective or pre-service PE teachers in a school impacts positively on learning about inclusive pedagogies and, consequently, the educational experiences of pupils with disabilities. Purpose: We used a special school placement and created opportunities for students to critically reflect on situated learning experiences to challenge normative perceptions of pedagogy and facilitate their learning about more inclusive approaches to teaching and learning. Specifically, we explore the influence of a special school placement on prospective PE teachers' learning about inclusive pedagogies. Methodology: Twenty-six first year undergraduate students, all of whom aspired to become PE teachers, participated in focus group interviews and were selected because they had attended a placement in a special school. Interviews were transcribed verbatim and analysed thematically. Findings: The findings were underpinned by situated learning theory and suggested, for the first time in research terms, that through a special school placement prospective PE teachers learned about: adapting activities; breaking activities into smaller, more manageable parts; demonstrating activities; pacing the delivery of activities; when to repeat activities; non-verbal communication; and managing disruptive behaviours. We conclude by arguing that this pedagogical learning will contribute to preparing our participants for teacher education programmes and a career teaching PE, given that it aligns with the criteria used to judge the performance of pre- and in-service teachers in England (see Department for Education (DfE). 2011. Teachers' Standards . London: DfE. https://assets.publishing.service.gov.uk/government/uploads/system/uploads/attachment_data/file/665520/Teachers__Standards.pdf ). Thus, we advocate for such placements to become a more frequent feature of the learning experiences of prospective and pre-service teachers. However, we do question and therefore call for future research that explores the longer-term influence and transferability of what is learned during special school placements.